Systematic literature review: Gdevelop-based game learning - Shubah Shofia; Hamsi Mansur; Qomario Qomario (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2026)
The game learning media based on GDevelop is a new solution that complies with the constructivist principles of learning effectiveness improvement. The proposed investigation is aimed at a Systematic Literature Review (SLR), which can be used to explore the empirical conditions, patterns of use, and viability of GDevelop as a platform to create educational media. The SLR methodology implied searching the Google Scholar and Publish or Perish databases within the period of 2020-2025. The selection of thirteen studies that met the inclusion criteria was followed by thematic analysis to synthesize the findings of the studies. The review shows that GDevelop has a consistent positive effect on the mathematical reasoning, conceptual understanding, and motivational interest of students of various levels of education. Additionally, the platform is considered practical and viable by both the media experts and the end-users. However, there are some challenges in the practice of implementation especially in the capabilities of educators to use and incorporate the tool in the curriculum. This study, therefore, suggests specific teacher training, content development based on the curriculum, and long-term research to determine the effectiveness of GDevelop in a wider range of learning conditions. Abstrak. Pemanfaatan media pembelajaran game yang dikembangkan melalui GDevelop merupakan metodologi progresif yang sesuai dengan paradigma konstruktivis, yang bertujuan untuk meningkatkan kemanjuran pendidikan. Investigasi ini berusaha untuk melakukan tinjauan literatur sistematis (SLR) untuk memeriksa secara kritis kondisi empiris, aplikasi, dan kelangsungan hidup GDevelop sebagai media untuk penciptaan sumber daya pendidikan. Metodologi SLR melibatkan pencarian komprehensif untuk artikel ilmiah dalam database Google Scholar dan Publish or Perish, dengan fokus pada publikasi dari periode 2020 hingga 2025. Dari 13 artikel yang memenuhi kriteria inklusi yang telah ditentukan, analisis tematik dilakukan untuk mengintegrasikan dan mensintesis hasil. Temuan menunjukkan bahwa GDevelop secara konsisten menunjukkan kemanjuran dalam meningkatkan kemampuan penalaran matematika siswa, pemahaman konseptual, dan motivasi untuk belajar di berbagai tingkatan pendidikan. Selain itu, platform ini dianggap layak dan praktis oleh para ahli di media dan penggunanya. Namun demikian, penerapannya dalam praktik menghadapi hambatan, terutama sehubungan dengan kompetensi pendidik dalam memanfaatkan dan menanamkannya dalam kurikulum yang ada. Akibatnya, penelitian ini menganjurkan penyediaan pengembangan profesional untuk pendidik, pembuatan konten yang selaras dengan standar kurikuler, dan perlunya penelitian tambahan untuk menyelidiki kemanjuran GDevelop di berbagai pengaturan pendidikan yang lebih luas.